Photocatalytic degradation of methylene blue using TiO2 supported in ceramic material - de Mello Peters, Raul Fernando; Mantey dos Santos, Pâmela Andréa; Machado, Tiele Caprioli; Rodriguez Lopez, Diosnel Antonio; Machado, Ênio Leandro; Lawisch Rodriguez, Adriane de Assis (Eclética Química, 2018)
The present work evaluates the use of ceramic material, produced with the aid of industrial waste through the Gel-Casting method, as a support for catalysts in the photocatalytic degradation of Methylene Blue. The analysis was carried out in a reactor containing UVC lamps through batch processing. The results show that the reaction of photocatalytic degradation of the dye presents pseudo-first order kinetics, with values of degradation between 60 and 70 %. The study evaluated the deactivation of the catalysts synthesized and supported in the ceramic material. In this case, it was observed that the larger the mass of deposited catalyst on the ceramic support, the longer the lifespan of the sample, since a larger mass takes longer to deactivate.